2006
DOI: 10.1007/s11258-006-9164-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and persistence of target species in newly created calcareous grasslands on former arable fields

Abstract: The effects of different restoration measures and management variants on the vegetation development of newly created calcareous grasslands were studied in southern Germany from 1993 to 2002. In 1993, fresh seed-containing hay from a nature reserve with ancient calcareous grasslands was transferred onto ex-arable fields with and without topsoil removal. Nine years after start of the restoration, the standing crop was lower and the cover of bare soil was higher on topsoil-removal sites than on sites without soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 34 publications
(39 reference statements)
7
60
0
Order By: Relevance
“…Microbial community dynamics in soils are closely linked to vegetation and soil characteristics (Marschner et al, 2001), yet, although plant succession is well documented, for instance in the re-establishment of chalk grasslands (Kiehl and Pfadenhauer, 2007), little is known about accompanying responses in microbial community structure. We therefore studied two seminatural Dutch chalk grassland sites (Gerendal nature reserve and Wrakelberg), which each contain several stages of secondary vegetation succession due to the abandonment of intensive agriculture at different times in the past (17 to 466 years) (Supplementary material and methods), thereby representing ideal field experiments to study soil-borne microbial community shifts.…”
mentioning
confidence: 99%
“…Microbial community dynamics in soils are closely linked to vegetation and soil characteristics (Marschner et al, 2001), yet, although plant succession is well documented, for instance in the re-establishment of chalk grasslands (Kiehl and Pfadenhauer, 2007), little is known about accompanying responses in microbial community structure. We therefore studied two seminatural Dutch chalk grassland sites (Gerendal nature reserve and Wrakelberg), which each contain several stages of secondary vegetation succession due to the abandonment of intensive agriculture at different times in the past (17 to 466 years) (Supplementary material and methods), thereby representing ideal field experiments to study soil-borne microbial community shifts.…”
mentioning
confidence: 99%
“…New patches with different origins (conversion of arable fields, clearing in forests or creation of new road verges) did not exhibit different colonization credit, suggesting that species richness may recover equally whatever the origin of the patch creation. This result is particularly unexpected as calcareous grassland restoration from arable land was shown to be difficult without strong management such as topsoil removing and/or hay addition (Walker et al 2004;Edwards et al 2007;Kiehl & Pfadenhauer 2007;Piqueray & Mahy 2010). Moreover, Gibson and Brown (1992) showed that former arable grasslands still differ from ancient grasslands in their floristic composition after decades, which was not the case in our study.…”
Section: Spatio-temporal Dynamics Of Calcareous Grasslandsmentioning
confidence: 99%
“…Top soil removal has been carried out in different non-forest habitat types in Western Europe where the reduction of nutrient levels is also necessary, such as fens [32], heathlands [33][34][35] and dry grasslands [36]. To date, however, studies on the effectiveness of top soil removal in saline habitats are lacking, despite the fact that it can be applied on a more local scale than other restoration methods (e.g.…”
Section: Introductionmentioning
confidence: 99%